Fiqh of diversity in the frame of tolerance as a pillar of indonesian integrity - Agustiar; Zaid Barzenji; Ali Saif; Bassam Badar Ja'far Al Kutsairi; Umar Ahmad Salem; Ibrahim bin Salem (Yayasan Azhar Amanaa Yogyakarta, 2024)
Abstract This article discusses the construction of diversity jurisprudence in the context of tolerance as a pillar of the integrity of the Unitary State of the Republic of Indonesia. By exploring fiqh thoughts from various schools of thought, the importance of tolerance in caring for the diversity of religions and beliefs in Indonesia. The focus is on how understanding fiqh can be the basis for tolerance in heterogeneous religious life in Indonesia. This research is a literature study that uses qualitative methods. The approach used is descriptive analysis to describe research objects based on facts in the literature. This method allows for an in-depth study of the subject under study. The findings of this research state that 1) An attitude of tolerance and openness in responding to differences of opinion in jurisprudence is an integral part of universal Islamic teachings. 2) The Prophet implemented a pattern of resolving differences of opinion respectfully, where each party has arguments that are respected and considered fairly. 3) The importance of dialogue, open discussion and empathy in dealing with differences of opinion as part of the rich and diverse Islamic intellectual tradition. 4) An attitude of tolerance towards differences in jurisprudential opinion has a significant impact on the harmony and unity of religious communities in Indonesia. The implications of this research include building awareness of the importance of tolerance in maintaining the integrity of the country, strengthening the foundations of an inclusive nation, and avoiding potential conflict in a diverse society.